H HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN MOTIVASI PERAWAT TERHADAP PELAKSANAAN EWS DI RSUD X - Julianto, Julianto (LPPM Universitas Sari Mulia, 2022)
Background: The high mortality rate in the hospital can be prevented with prompt and appropriate help. In the world, an early detection scoring system has been introduced using the Early Warning Score (EWS). The success of the EWS in reducing the incidence of cardiac arrest is influenced by the good implementation of the EWS instrument. A good implementation is influenced by several factors including knowledge and motivation. Objective: The research objective was to analyze The Relationship Between The Level Of Knowledge And Motivation Of Nurses In The Implementation Of EWS At Hospital. Method: This study used the Cross Sectional method, the population of inpatient nurses at Hospital, 43 samples, total sampling technique. The instrument questionnaire and observation sheet and used the Spearman rank test. Result: The results showed that the level of knowledge was good for 31 people (72%), enough motivation for nurses (93.1%) and the implementation of the EWS was good and sufficient for 40 people (95.4%). There is a relationship between the level of knowledge and motivation of nurses on the implementation of EWS at Hospital X. Knowledge level P = 0.018 (p <Î±) with a value of r = 0.358, motivation level P = 0.042 (p <Î±) with a value of r = 0.312. Conclusion: Providing regular EWS training as well as providing rewards and increasing incentives for nurses is very good for increasing knowledge and motivation so that the implementation of EWS can always be maximized.